Pengaruh Profitabilitas Pertumbuhan Perusahaan dan Struktur Aset Terhadap Kebijakan Hutang pada Perusahaan Sektor Consumer Cyclical di BEI - Rut Elpina BR Nababan; Astohar Astohar (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2024)
The main issue addressed in this research concerns the importance of selecting the appropriate funding sources for companies, particularly in the Consumer Cyclicals sector, which requires substantial financing to support operational activities. This study aims to analyze the influence of profitability, company growth, and asset structure on debt policy in Consumer Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study employs purposive sampling, yielding 190 observations from companies that meet the criteria. Multiple linear regression is used as the analytical tool to examine the relationships among the variables. The results indicate that asset structure has a positive and significant effect on corporate debt policy, demonstrating that companies with a stronger asset base tend to adopt higher levels of debt financing. In contrast, profitability and company growth do not show a significant effect on debt policy, suggesting that these financial performance indicators may not be the primary determinants in the capital structure decisions for Consumer Cyclicals firms. These findings highlight the critical role of asset management in debt strategy while emphasizing that profitability and growth alone may not suffice to guide financing choices. Companies should consider the composition of assets carefully when determining their debt policies to optimize financial stability and operational efficiency.